2021
DOI: 10.3390/cancers13122867
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Service Utilization and Advance Care Planning for Adult Glioblastoma Patients: A Systematic Review

Abstract: Glioblastoma (GBM) has a median overall survival of 16–21 months. As patients with GBM suffer concurrently from terminal cancer and a disease with progressive neurocognitive decline, advance care planning (ACP) and palliative care (PC) are critical. We conducted a systematic review exploring published literature on the prevalence of ACP, end-of-life (EOL) services utilization (including PC services), and experiences among adults with GBM. We searched from database inception until 20 December 2020. Preferred re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 45 publications
2
13
0
1
Order By: Relevance
“…Only a small proportion of HPs noted all patients were referred to palliative care. A systematic review of palliative care utilisation by glioblastoma patients identified advance care planning for up to half of patients, palliative care referrals and consultations for a third, and hospice referrals for most, with variable hospice use (38–86%) [ 35 ]. Although it is unclear from our survey whether low referral rates impacted the use of Advance Care Planning, such planning helps meet patients’ end of life preferences and reduces healthcare costs in patients with cognitive impairment or dementia [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a small proportion of HPs noted all patients were referred to palliative care. A systematic review of palliative care utilisation by glioblastoma patients identified advance care planning for up to half of patients, palliative care referrals and consultations for a third, and hospice referrals for most, with variable hospice use (38–86%) [ 35 ]. Although it is unclear from our survey whether low referral rates impacted the use of Advance Care Planning, such planning helps meet patients’ end of life preferences and reduces healthcare costs in patients with cognitive impairment or dementia [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“… On the left, an illustration of the different cell populations composing glioblastoma and its microenvironment, as well as associated blood-brain barrier disruption. On the right, a summary of the different areas covered by the articles in this Special Issue: GBM cells, stem cells, and preclinical studies [ 2 , 3 , 4 , 5 , 6 ], clinical studies [ 7 , 8 ], immunotherapy and new treatments [ 9 , 10 , 11 , 12 ]. Created with BioRender.com.…”
Section: Figurementioning
confidence: 99%
“…Eleven papers are included in this issue [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], and they range from in vitro and preclinical studies to clinical studies, and to immunotherapy and new potential treatments for glioblastomas ( Figure 1 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Although palliative care utilization for patients with glioblastoma has significantly increased in recent years, it is still underutilized in those with severe neurologic symptoms and a poor prognosis. 18 Our study aimed to assess the differences in healthcare utilization within 1 year before death between patients with glioblastoma who received palliative care and who did not, using the data collected retrospectively from the Taiwan Cancer Registry.…”
Section: Introductionmentioning
confidence: 99%